Vibration And Noise Attenuation On A Straight Chain Conveyor System - Voon, Zhen Liang (Universiti Sains Malaysia, 2019)
The conveyor noise is shown to be a composite of noise generating mechanisms, such as impacts between the chain and the idler roller, impacts on the sidewalls, impacts on the flex plate, frictional scraping and structure-borne vibration. In this project, the FlexMove FL 150 series conveyor system was studied. This conveyor system encountered periodical noise issues where the highest SPL was recorded at the right joint and the leg support with 81 – 83 dBA. This research aims to ascertain the source of the dominant noise during operation and subsequently, propose a solution to attenuate the sound pressure level. Three approaches for expressing the noise radiation were conducted – offline vertical and lateral clearance measurement and combined measurements of laser displacement, acceleration and microphone sound pressure level. Fast Fourier Transform (FFT) was performed on some measured parameters to identify the relevant frequency. Experimental results revealed that the dominant noise in the lower portion of the conveyor was mainly caused by the vertical displacement of the travelling chain units, resulting in the slapping of the chain units onto the slide rail. To reduce the impact force, a soft layer was installed on the slide rail to absorb the impact. This reduces the peak impact. After the adoption of Polymer A onto several segments of the slide rails, the sound pressure level and the structural acceleration had been successfully reduced by 4.4 dB and 86.27% respectively.